Immune-modulating Activity of Hydrogel Microparticles Contributes to the Host Defense in a Murine Model of Cutaneous Anthrax - Teunis, Allison L.; Popova, Taissia G.; Espina, Virginia; Liotta, Lance A.; Popov, Serguei G. (Frontiers in Molecular Biosciences, 2017)
We recently reported that the open-mesh (0.7 micron) polyacrylamide microparticles (MPs) with internally-coupled Cibacron affinity dye demonstrate protective effect in mice challenged into footpads with high doses (200 LD50) of anthrax (Sterne) spores. A single injection of MPs before spore challenge reduces inflammatory response, delays onset of mortality and promotes survival. In this study we show that the effect of MPs was substantially increased at the lower spore dose (7 LD50). The inflammation of footpads was reduced to the background level, and 60% of animals survived for 16 days while all untreated infected animals died within 6 days with strong inflammation. The effects of MPs were promoted when the MPs were loaded with a combination of neutrophil-attracting chemokines IL-8 and MIP-1α which delayed the onset of mortality in comparison with untreated mice for additional 8 days. The MPs were not inherently cytotoxic against the bacteria or cultured murine Raw264.7 cells, but stimulated these cells to release G-CSF, MCP-1, MIP-1α and TNF-α. Consistent with this finding the injection of MPs induced neutrophil influx into footpads, stimulated production of TNF-α associated with migration of ERK1/2-positive cells with the Langerhans phenotype from epidermis to regional lymph nodes. Our data support the mechanism of protection in which the immune defense induced by MPs along with the exogenous chemokines counterbalances the suppressive effect caused by anthrax infection.